The Grand Old Man and the Great Tradition Essays on Tanizaki Jun'ichiro in Honor of Adriana Boscaro - Blenati, Luisa; Ruperti, Bonaventura (University of Michigan Press, 2020)
Adriana Boscaro and Tanizaki Jun'ichirô: two names firmly linked in my mind and in those of many others who feel connected to Boscaro either on a personal level or through a shared devotion to the work of Tanizaki. This book is primarily conceived as an homage to both the work of the "grand old man," in all its inexhaustible richness, and to Boscaro's tireless contributions to the study of Tanizaki in Italy and around the world.